Personality questionnaires in personnel selection: to what extent applicants fake and how effective are they at it? - Parmač Kovačić, Maja (2010)
One of the main objections to the use of personality questionnaires in personnel selection is their susceptibility to faking ; i. e. responding which does not reflect the real estimation of candidate’s personality but his willingness to create a positive self-presentation. Research shows that this intentional response distortion does not influence construct or criterion validity of the personality questionnaires (Bradley & Haustein, 2006 ; Barrick & Mount, 1996), but lowers the quality and fairness of selection decisions (Rosse, Stecher, Miller & Levin, 1998). Since the problem of intentional response distortion on personality questionnaires is very important in personnel selection, the aim of this study is to determine the extent to which applicants in personnel selection fake on personality questionnaires and how effective are they at it. Three independent samples participated in the study. All of the participants filled-in the five-factor personality questionnaire (IPIP-100) in one of the three motivational situations: honest responding (N=370), simulated (N=267) and real (N=602) selection situation for military pilot. In the situation of honest responding and simulated selection situation participants were students at the University of Zagreb, and they have filled-in the questionnaire during the class. While in the situation of honest responding participants were told to fill-in the questionnaire completely honestly, in the simulated selection situation participants were given instruction not to respond honestly but to present themselves as an ideal candidate for a military pilot. In the real selection situation participants were candidates for military pilot position, and they have filled-in the questionnaire within the standard selection test battery. In order to test the efficacy of faking, we have also collected the expert estimations (N=11) about the desired level of every personality dimension within the five-factor model that an ideal military pilot has to have. In order to determine the extent to which candidates in a selection situation distort their answers on personality questionnaires, we compared the results of participants in the real selection situation with those in the situation of honest responding and the simulated selection situation. Comparison of participants’ results in the real selection situation with those in the situation of honest responding showed that candidates in the real selection situation present themselves more extraverted, more conscious, more emotionally stable and having a broader intellect. Considering that all the differences are statistically significant and have large effect sizes, we can conclude that they are probably not the result of real differences between two groups, but the result of intentional response distortion. Furthermore, comparison of participants’ results in two selection situations showed that participants in the real selection situation present themselves as less emotionally stable, less conscious and having a broader intellect. These differences are also statistically significant and with large effect sizes, so we can conclude that candidates in the simulated selection situation distort their answers more on these personality dimensions than the candidates in the real selection situation. In order to determine how effective candidates are at response distortion on personality questionnaires, we compared expert estimations about the desired level of every personality dimension in an ideal candidate for military pilot with participants’ results in three motivational situations. Although personality profiles of participants in two selection situations are more similar to the profile of an ideal candidate for military pilot than the personality profile of participants in the situation of honest responding, both of these profiles are numerically different from the expert estimations profile. More precisely, candidates in two selection situations present themselves as less emotionally stabile, more conscious and as having a narrower intellect. Generally speaking, obtained results show that candidates in the real selection distort their responses on personality questionnaires, although they do it to a lesser extent than participants in the simulated selection situation. Although personality profiles in the real and the simulated selection situation do not correspond completely with the criterion expert profile, results suggest that candidates can, to a certain extent, distort their answers in the direction of a specific personality profile.